2021
DOI: 10.1088/1755-1315/880/1/012031
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing canopy height variations in secondary tropical forests of Malaysia using NASA GEDI

Abstract: Tropical forests play a significant role in regulating the average global atmospheric temperature encompassing 25 % of the carbon present in the terrestrial biosphere. However, the rapid change in climate, arising from unsustainable human practices, can significantly affect their carbon uptake capability in the future. For understanding these deviations, it is important to identify and quantify the large-scale canopy height variations arising from previous anthropogenic disturbances. With the advent of NASA GE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…In this study, we validated the GEDI relative height metrics (rh50, rh75, rh90, rh95, rh100) using different resampling approaches (mean, 90th percentile, max aggregation) over different spatial resolutions (GEDI footprint level, 30, 90, 250, 1000 m) to derive the representative proxy of maximum canopy height over the Malaysian tropical forest based on GEDI L2A data. The study confirmed that canopy height obtained from GEDI has a strong correlation with ALS data over the different sites, as shown in previous studies, and thus, it is useful to assess canopy height variation across landscapes [49][50][51][52][53].…”
Section: Gedi Validation and Resamplingsupporting
confidence: 89%
See 1 more Smart Citation
“…In this study, we validated the GEDI relative height metrics (rh50, rh75, rh90, rh95, rh100) using different resampling approaches (mean, 90th percentile, max aggregation) over different spatial resolutions (GEDI footprint level, 30, 90, 250, 1000 m) to derive the representative proxy of maximum canopy height over the Malaysian tropical forest based on GEDI L2A data. The study confirmed that canopy height obtained from GEDI has a strong correlation with ALS data over the different sites, as shown in previous studies, and thus, it is useful to assess canopy height variation across landscapes [49][50][51][52][53].…”
Section: Gedi Validation and Resamplingsupporting
confidence: 89%
“…They found that the water limitation hypothesis was able to better explain the variance in canopy heights in tropical forests in China, while the same was true for the energy limitation hypothesis in temperate forests [11]. In another study, Fricker et al [14] made use of airborne LiDAR, often referred to as airborne laser scanning (ALS), for studying the association between canopy height and environmental variables (soil bulk density, pH, topographic wetness index, slope curvature and potential solar radiation) at six different spatial scales (25,50,100,250, 500, 1000 m) across an elevational gradient ranging from 200 to 3000 m above sea level (a.s.l.) in the Sierra Nevada mountains in the USA.…”
Section: Introductionmentioning
confidence: 99%
“…Remote sensing technologies have been proved to be highly effective for acquiring the forest structure at regional and even global scales. Passive optical sensor and active radar systems can mainly obtain canopy height and stem volume, but vertical forest structural information is still missing due to poor penetration [5][6][7][8]. Light detection and ranging (lidar) is an active remote sensing technique that can overcome such problems and accurately represent vertical forest structure and underlying topography.…”
Section: Introductionmentioning
confidence: 99%
“…In Madre de Dios, during the same period, the rate was 13,584.15 ha/yr −1 [19]. Forest loss reduces the production of organic matter [1,2,20], generates carbon emissions into the atmosphere [21], contributes to climatic variability, and decreases water storage in the atmosphere and in soils [21]. Nevertheless, the effects of specific disturbances on forest ecosystems vary considerably, depending on their scale and frequency [22].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the effects of specific disturbances on forest ecosystems vary considerably, depending on their scale and frequency [22]. Furthermore, deforestation causes changes in seed and fruit production [10] and leads to forest desiccation and changes in its floristic composition [21,23].…”
Section: Introductionmentioning
confidence: 99%